Experimental and numerical studies on the corrosion properties of AISI 316L stainless steel in two-phase upward slug flows. Issue 1 (1st January 2020) - Lv, Wenchao; Ou, Guofu; Liu, Xiaofei; Gong, Chengcheng
Abstract : The corrosion properties of AISI 316L stainless steel in upward slug flow were initially investigated using the electrochemical measurements and computational fluid dynamics (CFD) simulations. The results demonstrate that the slug flow may destroy the passivation film on the specimen surface due to its intermittency and volatility, accelerating the pitting corrosion process on the electrode surface. It results in a higher corrosion rate in the two-phase slug flow than in the single-phase flow. The variations of superficial velocity lead to changes in the slug flow configuration. The variation has a greater impact on the Taylor bubble than the liquid slug. The changes in slug flow configuration result in differences in shear stress and mass transfer coefficient, leading to corresponding differences in electrochemical properties of AISI 316L stainless steel.